Surface reformed anisotropic polystyrene‐block‐poly(ethylene‐ran‐butylene)‐block‐polystyrene‐graft‐maleic anhydride layer via ion‐beam irradiation for liquid crystals. (7th May 2022) - Kim, Dong Hyun; Lee, Dong Wook; Oh, Jin Young; Won, Jonghoon; Seo, Dae‐Shik
Abstract: The surface modifications and liquid crystal (LC) alignment properties of polystyrene‐ block ‐poly(ethylene‐ ran ‐butylene)‐ block ‐polystyrene‐ graft ‐maleic anhydride (SEBS‐g‐MA) films induced by ion‐beam (IB) irradiation are reported herein. Changes to the surfaces of the SEBS‐g‐MA films from IB irradiation at various incidence angles and changes in the LC orientations upon LC cell fabrication were analyzed. The physical surface modifications due to IB irradiation were observed via atomic force microscopy. Additionally, changes in the molecular composition of the surface were observed through X‐ray photoelectron spectroscopy analysis. Polarized optical microscopy analysis shows that excellent LC alignment properties could be obtained after IB irradiation at angles exceeding 45°. Further, the anisotropy caused by IB irradiation was more responsible for uniform LC alignment than the corrugated pattern.